Effects of wood texture and color on aesthetic pleasure: two experimental studies - Dai, Zetian; Xue, Juan; Wang, Shoushan (Institute of Advanced Engineering and Science, 2023)
The texture and color on wood are key factors that influence an individual's perception of it. However, little research has been done to confirm what kind of pattern in textures and colors are more likely to evoke individual aesthetic pleasure. Therefore, twenty-four decorative wood from northern China were selected, identified, and quantified in their colors with a CR-5 Colorimeter. We picked out eight kinds of wood with optimal texture characteristics through feature-fusion wood grain recognition (FWGR) and enhanced the texture features with photoshop in VR space. The result show that, in the color dimension, woods in the hue range of 20-25 and saturation of 65-75 were considered beautiful for individual perception of aesthetic. In the texture dimension, the size of the space affects the individual's preference for texture. When the pattern of the wood ray is continuous and clear, the individual's perception of its fluidity is enhanced; while for the fuzzy and interrupted pattern of the wood ray, the individual does not follow the fluidity of the line but focuses on the overall uniformity.